2021
DOI: 10.1021/acschemneuro.0c00758
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Based Approaches to Classify the Functional Impact of ZBTB18 Missense Variants in Health and Disease

Abstract: The Cys2His2 type zinc finger is a motif found in many eukaryotic transcription factor proteins that facilitates binding to genomic DNA so as to influence cellular gene expression. One such transcription factor is ZBTB18, characterized as a repressor that orchestrates the development of mammalian tissues including skeletal muscle and brain during embryogenesis. In humans, it has been recognized that disease-associated ZBTB18 missense variants mapping to the coding sequence of the zinc finger domain influence s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 88 publications
1
11
0
Order By: Relevance
“…Consistent with studies of the Rnd2 3′ enhancer, we found that wildtype ZBTB18 bound native sequences Id2 ‐bs1 and Id2 ‐bs2 with high affinity, while the N461S variant bound more strongly than wildtype ZBTB18 yet it does not form stable complexes with Id2 ‐bs2 (Blake et al, 2021). On the other hand, the R495G variant does not form stable complexes with Id2 ‐bs1 and binds Id2 ‐bs2 weakly (Blake et al, 2021). Therefore, disease‐associated ZBTB18 missense variants N461S and R495G disrupt sequence‐specific DNA binding that is essential for regulating the expression of downstream target genes Rnd2 and Id2 .…”
Section: Introductionsupporting
confidence: 88%
See 3 more Smart Citations
“…Consistent with studies of the Rnd2 3′ enhancer, we found that wildtype ZBTB18 bound native sequences Id2 ‐bs1 and Id2 ‐bs2 with high affinity, while the N461S variant bound more strongly than wildtype ZBTB18 yet it does not form stable complexes with Id2 ‐bs2 (Blake et al, 2021). On the other hand, the R495G variant does not form stable complexes with Id2 ‐bs1 and binds Id2 ‐bs2 weakly (Blake et al, 2021). Therefore, disease‐associated ZBTB18 missense variants N461S and R495G disrupt sequence‐specific DNA binding that is essential for regulating the expression of downstream target genes Rnd2 and Id2 .…”
Section: Introductionsupporting
confidence: 88%
“…luciferase reporter assays, chromatin immunoprecipitation (ChIP), electrophoretic mobility shift assays (EMSAs), in utero electroporation (IUE) studies; as well as as well as more recently reported screening methods (e.g. multi‐plex reporter assays (MPRAs) (Mulvey, Lagunas, & Dougherty, 2021), mammalian targeted damID (MaTaDa) (Cheetham et al, 2018), Cut&Run (Meers, Bryson, Henikoff, & Henikoff, 2019)) and, where feasible, binding free energy calculations (Blake et al, 2021; Hemming et al, 2019; Hemming et al, 2020)) in order to study the DNA‐binding, protein–protein interaction and transcriptional regulatory signalling properties of TFs as well as their query variants (Table 3). It is noteworthy that MPRAs, MaTaDa and Cut&Run leverage advances of recent years in massively parallel sequencing technologies and robotic screening platforms to make them exciting new functional screening approaches to map causal missense TF variants in health and disease.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The residue scanning/affinity maturation tool of Schrodinger Biologics Suite ( 58 ) was used to generate variants in US28 Toledo and assess their impact on binding to chemokines and the G protein assembly (i.e., all of the αβγ subunits), adapting our previous work ( 59 ). Calculations assessed changes in chemokine binding to the US28-G protein assembly (i.e., chemokine treated as ligand, US28-G protein assembly treated as receptor) and changes in G protein assembly binding to the chemokine-US28 assembly (i.e., αβγ assembly treated as ligand, chemokine-US28 assembly treated as receptor).…”
Section: Methodsmentioning
confidence: 99%